2016
DOI: 10.20950/1678-2305.2016v42n3p710
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos da reprodução e primeiro registro de distocia em raia-ticonha (Rhinoptera bonasus)

Abstract: The registration of reproductive processes of elasmobranchs is rare and little documented in public aquariums. The present work registers the first case of dystocia in cownose ray (Rhinoptera bonasus), (Mitchill, 1815). The ray maintained in captivity by 16 years, it presented a gestation of 14 months. There was not occurrence of the natural childbirth, being necessary the human intervention through obstetric maneuvers for the retreat of the fetus. The described procedures can be used as reference in other cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Although captive birth for females that were captured pregnant from the wild was reported by Gonzalez (2004), this is the first published report of captive birth with copulation occurring under human care. Births for the Z. brevirostris have been recorded in the Ubatuba Aquarium since 2002 (Baldassin et al ., 2008; Cavalcante et al ., 2016). From previous attempts of newborn care, the species seems to require a substrate that allows the animals to bury themselves, a natural behaviour that promotes greater welfare, once representing a camouflage behaviour against predators (Sousa Lima et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although captive birth for females that were captured pregnant from the wild was reported by Gonzalez (2004), this is the first published report of captive birth with copulation occurring under human care. Births for the Z. brevirostris have been recorded in the Ubatuba Aquarium since 2002 (Baldassin et al ., 2008; Cavalcante et al ., 2016). From previous attempts of newborn care, the species seems to require a substrate that allows the animals to bury themselves, a natural behaviour that promotes greater welfare, once representing a camouflage behaviour against predators (Sousa Lima et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although captive breeding is a common practice in zoos, in public aquariums there is still little engagement regarding the sustainability of animal population, with few institutions that have implemented breeding programmes for aquatic organisms (Buckley et al ., 2018; Daly & Jones, 2017; Henningsen et al ., 2017). In Brazil, the Ubatuba Aquarium was the first public aquarium to reproduce small‐sized elasmobranchs, such as Rhinoptera bonasus and Z. brevirostris (Baldassin et al ., 2008; Cavalcante et al ., 2016). From a conservation point of view, research and education are needed for the responsible management of elasmobranchs given the increasing declines in wild populations due to anthropogenic pressures (Daly & Jones, 2017; Kim et al ., 2020; Wyffels et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In one of the reported cases, the female was 16-year-old and the gestation lasted 14 months, two months longer than expected for the species. Human intervention was necessary, and obstetric maneuvers were performed, but the neonate was already dead and presented rigor-mortis (Cavalcante et al 2016). The authors argue that the probable causes were the advanced age of the female, the position of the neonate inside the uterus, as well as its superior size in relation to the ones previously generated by her.…”
Section: Discussionmentioning
confidence: 99%
“…When fetal, dystocia may be SHORT COMMUNICATION caused by the abnormal size, or inadequate position (Noakes et al 2001;Stedman & Garner 2018). Likewise, dystocia is commonly associated with high neonate mortality rates and, in extreme cases, can lead to maternal mortality (Mahon et al 2001;Jung-Schroers et al 2015;Cavalcante et al 2016). In elasmobranchs, reports are so far, restricted to captive animals, possibly because of the facility of monitoring pregnant females kept under human care (Henningsen et al 2004;George et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dystocia has been observed on multiple occasions for Cownose Rays in aquaria (Cavalcante et al, 2016;George et al, 2017), and it has also been suggested as a cause of mortality associated with capture for in situ rays (Leite et al, 2020). Procedures for cesarean delivery and monitoring have been developed for Cownose Rays, and, if adopted, should minimize neonate and female loss for animals in aquaria.…”
Section: Reproductive Pathologiesmentioning
confidence: 99%